Current Clinical Use of Reteplase for Thrombolysis: A Pharmacokinetic-Pharmacodynamic Perspective - Martin, Ulrich; Kaufmann, Burchard; Neugebauer, G??nter (Clinical pharmacokinetics, 1999)
Clinical evaluation of a new thrombolytic agent should start with a dose that provides adequate efficacy and has an acceptably low bleeding risk; this results in a narrow therapeutic window at the upper end of the dose-response curve. Angiographic patency of the infarct-related artery is still the clinical surrogate end-point for mortality in phase II dose-ranging studies. There is experimental and clinical evidence that the area under the concentration-time curve (AUC) for plasminogenolytic activity of a thrombolytic agent is positively correlated with patency of the infarct-related artery. Dose-ranging studies of the novel recombinant plasminogen activator reteplase in healthy volunteers enabled computation of a linear regression curve by which a clinical starting dose could be calculated for an adapted target AUC that would be clinically effective. Pharmacokinetic analysis also revealed that the half-life of reteplase is 4 times longer than that of the reference thrombolytic alteplase, thus allowing bolus injection. The suggested single bolus starting dose of 10U was supported by results from studies in a canine model of coronary thrombolysis. The feedback of insufficiently high patency rates compared with the increased efficacy of front-loaded and accelerated alteplase demanded optimisation strategies for reteplase. Animal experiments suggested that a double bolus regimen of reteplase would be preferable to doubling the single bolus dose. Pharmacokinetic modelling suggested a time interval of 30 min between the 2 bolus injections. Selection of the tested double bolus regimens was conservative and empirical. First, the previously tested single bolus of 15U was divided to 10 + 5U; secondly, the second bolus dose was increased to 10U. This strategy proved to be successful. The current dosage recommendation for reteplase is a double bolus intravenous injection of 10 + 10U, each over 2 min, 30 min apart. This produces a reduction in mortality in patients with acute myocardial infarction that is equivalent to that produced by front-loaded and accelerated infusion of alteplase.